Evaluation of Natural Bioactive-Derived Punicalagin Niosomes in Skin-Aging Processes Accelerated by Oxidant and Ultraviolet Radiation - Mohamad EA; Aly AA; Khalaf AA; Ahmed MI; Kamel RM; Abdelnaby SM; Abdelzaher YH; Sedrak MG; Mousa SA (Dove Medical Press, 2021)
Ebtesam A Mohamad,1 Aya A Aly,2 Aya A Khalaf,2 Mona I Ahmed,2 Reham M Kamel,2 Sherouk M Abdelnaby,2 Yasmine H Abdelzaher,2 Marize G Sedrak,2 Shaker A Mousa3 1Biophysics Department, Faculty of Science, Cairo University, Giza, Egypt; 2Biotechnology/Biomolecular Chemistry Program, Faculty of Science, Cairo University, Giza, Egypt; 3The Pharmaceutical Research Institute, Albany College of Pharmacy and Health Sciences, Rensselaer, NY, USACorrespondence: Shaker A MousaThe Pharmaceutical Research Institute, Albany College of Pharmacy and Health Sciences, Rensselaer, NY, 12144, USATel +1-518-694-7397Fax +1-518-694-7567Email shaker.mousa@acphs.eduIntroduction: Skin aging is a normal process that might be accelerated or delayed by altering the balance between antioxidants and free radicals due to increase in the exposure to reactive oxygen species (ROS) into skin cells via UV radiation. Antioxidants can neutralize the harmful effects of ROS, and secondary plant metabolites might help protect against UV radiation.Methods: In this study, punicalagin was extracted from pomegranate, and concentrations of total polyphenolics and flavonoids were determined, and antioxidant activities were measured. Punicalagin was loaded onto niosomes, and its morphology and release were studied. An in vitro study was performed on human fibroblast cell line HFB4 cells with aging induced by H2O2 and UV radiation. Cell cycle arrest was studied, and different genes (MMP3, Col1A1, Timp3, and TERT) involved in the skin aging process were selected to measure punicalagin's effect.Results: Punicalagin succeeded in reducing the growth arrest of HFB4 cells, activated production of the Col1A1 and Timp3 genes, maintained collagen level, and lowered MMP3. Punicalagin increased human TERT concentration in skin cells.Discussion: Punicalagin is promising as a natural antioxidant to protect human skin from aging.Keywords: skin aging, punicalagin, niosomes, UV radiation, collagen